1970
DOI: 10.3329/taj.v22i1.5019
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Awareness of Rural People About Currently Emerging Disease Bird Flu

Abstract: A descriptive type of cross-sectional study was conducted in a village Gohordo of Gabtoli Upazila, Bogra to assess the knowledge and awareness of people of age above 18 years and above about "bird flu", its modes of transmission and prevention, by an interviewer administered questionnaire. The questionnaire was pretested and data were collected using purposive sampling technique. In this study it was found that out of 418 people, 231(55.26%) were female and the rest 187 (44.74%) were male. Majority of the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…11 In the present study 90.4 percent of the respondents believed poultry workers as risk for infection which is in contrast to the study conducted by Alam MJ et al where only 30.97% subjects thought that poultry carrying conducted by Alam M J et al where literacy had significant influence on awareness. 12 This study reveled that males were significantly more aware than females, whereas in the study conducted by Marinos G et al in Greece in 2007 showed no relationship with gender. 9 This difference could be due to the fact that males usually had more interaction and socialization than females in our society.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…11 In the present study 90.4 percent of the respondents believed poultry workers as risk for infection which is in contrast to the study conducted by Alam MJ et al where only 30.97% subjects thought that poultry carrying conducted by Alam M J et al where literacy had significant influence on awareness. 12 This study reveled that males were significantly more aware than females, whereas in the study conducted by Marinos G et al in Greece in 2007 showed no relationship with gender. 9 This difference could be due to the fact that males usually had more interaction and socialization than females in our society.…”
contrasting
confidence: 49%
“…12 Direct contact with infected poultry or with surfaces and objects contaminated by their droppings is considered the main route of human infection. 7 In this study, Majority of subjects (84.9%) reported that the infection could result from keeping infected birds and poultry.…”
Section: Resultsmentioning
confidence: 99%
“…M Jahangir Alam et al [14] showed among 85.39% respondents know that the disease may transmit to human population. Among the people who heard the name of the disease [14].…”
Section: Resultsmentioning
confidence: 99%
“…M Jahangir Alam et al [14] showed among 85.39% respondents know that the disease may transmit to human population. Among the people who heard the name of the disease [14]. But when the knowledge of Mode of Transmission was assessed in the poultry rearing families it was seen that this knowledge was more in urban poultry owners (83.3%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation